Asian Inward and Outward FDI New Challenges in the Global Economy - Alvstam, C.; Dolles, H.; Strom, P.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Asian Inward and Outward FDI brings together both works from researchers in international business and economic geography. The book is aimed for both scholars with interest in macro and micro economic impact of new flows of FDI.
Keywords: Leadership; International business enterprises; Investment banking; Securities; Management; Industrial management; International economics; Business Strategy/Leadership.; International Business; Investments and Securities; Management; Innovation/Technology Management; International Economics